THE POVERTY IMPACT OF THE TOURISM INDUSTRY: A CASE STUDY OF LANGKAWI ISLAND, MALAYSIA - ROSLAN, A.H (ASEAN Journal on Hospitality and Tourism, 2007)
One of the main concerns in the development of the tourism industry in Malaysia is on the improvement and diversification of tourism âproductsâ in attracting tourists to Malaysia. This is understandable since the tourism industry is expected to generate and maximise foreign exchange earnings, increase income and creating employment. The question of poverty and the needs to encourage the poor to participate in the tourism industry is generally neglected in the formulation of tourism policies and strategies. Thus, the impact of the tourism industry on the poor is left mainly to the âtrickling downâ effects rather than a deliberate and careful planning to improve the impact of tourism on them. There are now emerging literatures suggesting that there exist a huge potential for making tourism to be effectively work for the poor. Consequently, this raises the need to examine, among others, the participation of the poor in the tourism industry as well as its impact on poverty. In this paper, we explore this issue for the case of Langkawi Island, an island that has been proclaimed as one of the major tourist attractions to Malaysia.